A dynamic approach to environmental compliance decisions in U.S. Electricity Market: The Acid Rain Program revisited. (July 2017) - Hancevic, Pedro Ignacio
Abstract: The Acid Rain Program (ARP) was implemented in 1995. Since then, coal-fired boilers have had to choose among three main compliance alternatives: purchase pollution permits; switch to an alternative lower-sulfur coal; or adopt a scrubber. This decision problem is driven by the evolution of several economic variables and is revised when significant changes (to prices, quality of inputs, output level, technology, transport costs, regulations, among others) occur. Using a structural dynamic discrete choice model, I recover cost parameters and use them to evaluate two different counterfactual policies. The results confirm there is a trade-off between fuel switching and scrubbing costs (with the latter having a higher investment cost and a lower variable cost), and also the existence of regional heterogeneity. Finally, the ARP implied cost savings of approximately 4.7 billions if compared to a uniform emission rate standard and 14.8 billions if compared to compulsory scrubbing for the 1995–2005 period. Abstract : Highlights: With the cap-and-trade system of the ARP boilers had three main compliance options. Purchase allowances; retrofit the boiler to burn low-sulfur coal; adopt scrubbers. We develop and estimate a rigorous structural dynamic discrete choice model. Trade-off between fuel switching and scrubbing (capital versus operating costs). Cost savings from the ARP were substantial if compared to previous regulations.